Trends in Dental Practice Sales and Associateships in the Current Economy - C. Steven Wolff (Wolters Kluwer Medknow Publications, 2011)
Recent experiences would suggest that there is a significant discrepancy in the number of doctors retiring and transitioning their practices and the number of younger practitioners wishing to assume ownership and build a career. Peaks and valleys in dental school enrollment over the last forty years should have produced an abundance of retirement aged doctors wishing to place their practices on the market to a smaller pool of buyers. Such is currently not the case. Doctors in their sixties have experienced recent stock market downturns in 2000 and 2008, the "9-11" tragedy and a drop in both the value and liquidity of the housing market. The ready access to refinance or second mortgage funds may even find some doctors upside down on personal, vacation and investment real estate. All of this combined has had considerable negative impact on their net worth. Health care costs continue to increase and most dentists are personally responsible for their premiums. Combine all of this with the current low level of secure returns on invested capital along with a significant increase in life expectancy over the last two generations and many decide they are simply unable to retire as planned. The fear of running out of money is stronger than their will to pursue retirement. This article examines in some detail the reasons for this imbalance and the effects they are having on practice transitions, practice values and the market for associate employment. We will also explore what the future may hold for both retiring and new career doctors.